Factors Controlling Velocity Variations at Short-Term, Seasonal and Multiyear Time Scales, Ritigraben Rock Glacier, Western Swiss Alps - Kenner, Robert; Phillips, Marcia; Beutel, Jan; id_orcid:0 000-0003-0879-2455; Hiller, Martin; Limpach, Philippe; Pointner, Eric; Volken, Martin (Permafrost and Periglacial Processes, 2017)
ISSN:1045-6740 ISSN:1099-1530